Seeing the wood for the trees: Social Science 3.0 and the role of visual thinking. Issue 1 (2nd January 2017) - Ravetz, Joe; Ravetz, Amanda
Abstract : Social Science is increasingly called on to address "grand challenges", "wicked problems", "societal dilemmas" and similar problematiques. Examples include climate change, the war on drugs and urban poverty. It is now widely agreed that the disciplinary structure of academic science, with its journals, curricula, peer communities, etc., is not well suited to such trans-disciplinary, ill-bounded, controversial issues, but the ways forward are not yet clear or accepted by the mainstream. The concept of a next generation paradigm of "Science 3.0" has emerged through work on sustainability systems analysis, and for this multiple channels for learning, thinking and communications are essential. Visual thinking in its many forms (from technical representation or mapping, to photography or video, to design or illustration, to fine art) can bring to the table tacit and "felt" knowledge, creative experience and links from analysis with synthesis. This paper first sketches the contours of a Social Science 3.0, and then demonstrates with examples how visual thinking can combine with rational argument, or extend beyond it to other forms of experience.